The Role of Collybistin in Gephyrin Clustering at Inhibitory Synapses: Facts and Open Questions - Papadopoulos, Theofilos; Soykan, Tolga (Frontiers in Cellular Neuroscience, 2011)
Collybistin (Cb) is a brain-specific GDP/GTP-exchange factor, which interacts with the inhibitory receptor anchoring protein gephyrin. Data from mice carrying an inactivated Cb gene indicate that Cb is required for the formation and maintenance of gephyrin and gephyrin-dependent GABAA receptor (GABAAR) clusters at inhibitory postsynapses in selected regions of the mammalian forebrain. However, important aspects of how Cb’s GDP/GTP exchange activity, structure and regulation contribute to gephyrin and GABAAR clustering, as well as its role in synaptic plasticity, remain poorly understood. Here we review the current state of knowledge about Cb’s function and address open questions concerning its contribution to synapse formation, maintenance, plasticity and adaptive changes in response to altered network activity.